Propuesta de intervención urbano-arquitectónica en el bien patrimonial de la Iglesia matriz de la ciudad de Zaruma - Aguilar Heredia, Orfa Alexandra (2024)
This project responds to the urgent need to safeguard and conserve the invaluable heritage of the Zaruma canton. Our focus is on the Iglesia Matriz "Santuario de la Virgen del Carmen," a property of immense historical, architectural, and heritage value. Given the precarious situation Zaruma finds itself in, an in-depth analysis is crucial for a subsequent urban architectural intervention. The urban study was a comprehensive examination of the church's immediate context, identifying and resolving issues affecting the sector. This thorough diagnosis led to a proposal that not only enhances the connections between the church, the city, and the country but also introduces a range of strategies for the cultural, heritage, environmental, and economic upliftment of the sector. The architectural diagnosis was a detailed historical, structural, and formal analysis. This analysis was crucial in determining the interventions and the state of conservation of the Church, which in turn informed the proposed intervention. The proposed intervention consists of potential solutions to the various injuries that the Church currently presents